Online Ordering System for Kumpulan Ikatan Perusahaan Sdn. Bhd. - Kandasamy, Pathmanathan (2002)
Kumpulan Ikatan Perusahaan Sdn Bhd which sells car products needs a website to provide ordering facilities through Internet as an effort to expand its market and to increase profit. At the same time, this web development pioneers the effort of e-commerce realization in future. Through this web site, users can browse product that are sold by Kumpulan Ikatan Perusahaan Sdn Bhd and then make online orders. The objective of this system is to promote products of Kumpulan Ikatan Perusahaan Sdn Bhd. The applications which will be developed id divided into two main module that is order module and Kumpulan Ikatan Perusahaan Sdn Bhd management module. Order module describes the online orders by customer and the management module describes management of Kumpulan Ikatan Perusahaan Sdn Bhd from the aspect of receiving orders, product deliveries, payment and updating of products and suppliers.